THE ROLE OF COMMUNICATIVE COMPETENCE IN YOUTH SOCIAL ACTIVISM (Archive of Conferences, 2021)
The article shows the current level of foreign language learning among young people and the impact of reforms in Uzbekistan on the competitiveness of the youth. Important aspects of learning a foreign language are expressed in the examples of folklore, in addition to content analysis based on the views of scientists, poets and theorists who lived and worked in different periods. The impact of learning a foreign language on the youth’s competitiveness is analyzed on the basis of statistical data based on various arguments on teaching foreign languages in New Uzbekistan. Moreover, based on the results of the study, conclusions are presented